Polymorphism of ompH gene of Pasteurella multocida serotype A strains isolated in Iran - OULAD, M.; TAHAMTAN, Y.; SOHRABI, N. (Journal of the Hellenic Veterinary Medical Society, 2018)
One of the most frequent causes of respiratory infection and death in sheep and goats is Pasteurella multocida. In humans, it has been associated with diseases of the respiratory tracts, arthritis, osteomyelitis and meningitis. Outer membrane protein H (OmpH) has a role in immunogenicity and pathogenicity of P. multocida. The aim of this study was to characterize the genetic diversity of ompH gene of a panel of P. multocida serotype A strains isolated in sheep. Forty P. multocida serotype A strains isolated in previous study were selected and analyzed by restriction fragment length polymorphism (RFLP) of a species-specific PCR assay. RFLP amplified fragment produced five different cleavage patterns. On the basis of combinations resulting from ompH gene digestion, the 40 P. multocida isolates were classified in six RFLP type. It seems that isolates with variants genetic profile represent different pathogenecity. New vaccine formulation should consider multivariants of P. multocida in order to confer a wider protection.